2002
DOI: 10.1073/pnas.032523999
|View full text |Cite
|
Sign up to set email alerts
|

An iron-regulated sortase anchors a class of surface protein during Staphylococcus aureus pathogenesis

Abstract: Sortase (SrtA), an enzyme that anchors surface proteins to the cell wall of Gram-positive bacteria, cleaves sorting signals at the LPXTG motif. We have identified a second sortase (SrtB) in the Gram-positive pathogen Staphylococcus aureus that is required for anchoring of a surface protein with a NPQTN motif. Purified SrtB cleaves NPQTN-bearing peptides in vitro, and a srtB mutant is defective in the persistence of animal infections. srtB is part of an iron-regulated locus called iron-responsive surface determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
361
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 346 publications
(368 citation statements)
references
References 45 publications
(45 reference statements)
6
361
0
1
Order By: Relevance
“…(33,39). By contrast, SrtB had no detectable activity against the LPETG substrate, even after 12 h at 37°C and an enzyme concentration of 94.8 M. This is consistent with earlier studies in which no LPETG-cleaving activity was observed for SrtB in vitro (22). SrtLS was able to hydrolyze the LPETG substrate but with a vastly reduced k cat /K m app of 3.7 Ϯ 0.6 ϫ 10 Ϫ4 M Ϫ1 s Ϫ1 (Table 2).…”
Section: Motifsupporting
confidence: 82%
See 3 more Smart Citations
“…(33,39). By contrast, SrtB had no detectable activity against the LPETG substrate, even after 12 h at 37°C and an enzyme concentration of 94.8 M. This is consistent with earlier studies in which no LPETG-cleaving activity was observed for SrtB in vitro (22). SrtLS was able to hydrolyze the LPETG substrate but with a vastly reduced k cat /K m app of 3.7 Ϯ 0.6 ϫ 10 Ϫ4 M Ϫ1 s Ϫ1 (Table 2).…”
Section: Motifsupporting
confidence: 82%
“…SrtA anchors LPXTGcontaining proteins, whereas SrtB is specific for NPQTN-containing proteins (22,26). In order to better understand the basis for this specific recognition, we used sequence analysis to look at SrtA and SrtB isoforms from various Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sortase A cleaves secreted protein at LPXTG sorting signals and recognizes the amino group of lipid II peptidoglycan precursors as a nucleophile (8,9). Sortase B cleaves protein substrates at NPQTN sorting signals (10). This enzyme immobilizes proteins within fully assembled cell walls, utilizing the cell wall cross-bridge as a nucleophile (11).…”
mentioning
confidence: 99%